2020
DOI: 10.1111/gcb.15431
|View full text |Cite
|
Sign up to set email alerts
|

Recovery disparity between coral cover and the physical functionality of reefs with impaired coral assemblages

Abstract: The ecology and structure of many tropical coral reefs have been markedly altered over the past few decades. Although long‐term recovery has been observed in terms of coral cover, it is not clear how novel species configurations shape reef functionality in impaired reefs. The identities and life‐history strategies of the corals species that recover are essential for understanding reef functional dynamics. We used a species identity approach to quantify the physical functionality outcomes over a 13 year period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 90 publications
(166 reference statements)
1
50
0
4
Order By: Relevance
“…In addition, the loss of highly susceptible coral species may also trigger an abrupt decrease in the accretion (growth) of the reef framework (Estrada-Saldívar et al, 2020), as most of the highly susceptible species to SCTLD are also important reef builders. A shift in the composition of reefbuilding corals and reef structure may not only compromise ecosystem resilience through a reduction in functional traits (González-Barrios et al, 2020;Molina-Hernández et al, 2020) but may also affect many other reef-associated species (Idjadi and Edmunds, 2006;Rogers et al, 2014). Given the short-temporal scale of our study, we cannot conclude that the drastic changes observed in the ecological communities will lock Cozumel reefs into low-carbonate production and high algae dominated states.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, the loss of highly susceptible coral species may also trigger an abrupt decrease in the accretion (growth) of the reef framework (Estrada-Saldívar et al, 2020), as most of the highly susceptible species to SCTLD are also important reef builders. A shift in the composition of reefbuilding corals and reef structure may not only compromise ecosystem resilience through a reduction in functional traits (González-Barrios et al, 2020;Molina-Hernández et al, 2020) but may also affect many other reef-associated species (Idjadi and Edmunds, 2006;Rogers et al, 2014). Given the short-temporal scale of our study, we cannot conclude that the drastic changes observed in the ecological communities will lock Cozumel reefs into low-carbonate production and high algae dominated states.…”
Section: Discussionmentioning
confidence: 82%
“…Red lines represent the mean of 500 stochastic projections (depicted as thin light red lines) based on the population growth rate (λ) derived from the IPMs with fecundity reduced to half (λ = 1.038 for D. favus and λ = 0.948 for P. lamellina) traits frequently express ecological functionality (Madin et al, 2016;Mouillot et al, 2013), there is an increasing interest in heuristically categorizing corals for comparative purposes. For example, some studies emphasize 'weedy' versus 'non-weedy' (Knowlton, 2001), or massive versus branching morphologies (Álvarez-Noriega et al, 2016;Comeau et al, 2014;Klepac & Barshish, 2020;Loya et al, 2001;Pisapia et al, 2020), or some other multi-dimensional trait measures (Darling et al, 2012;Denis et al, 2017;González-Barrios et al, 2020;van Woesik, Franklin, et al, 2012). In most cases, studies using trait categories largely aim to estimate 'winners' and 'losers' (sensu Loya et al, 2001), or differential functionality following disturbances and ecosystem-wide changes (Denis et al, 2017;González-Barrios et al, 2020;Mouillot et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For example, some studies emphasize 'weedy' versus 'non-weedy' (Knowlton, 2001), or massive versus branching morphologies (Álvarez-Noriega et al, 2016;Comeau et al, 2014;Klepac & Barshish, 2020;Loya et al, 2001;Pisapia et al, 2020), or some other multi-dimensional trait measures (Darling et al, 2012;Denis et al, 2017;González-Barrios et al, 2020;van Woesik, Franklin, et al, 2012). In most cases, studies using trait categories largely aim to estimate 'winners' and 'losers' (sensu Loya et al, 2001), or differential functionality following disturbances and ecosystem-wide changes (Denis et al, 2017;González-Barrios et al, 2020;Mouillot et al, 2013). While such approaches yield valuable insights, they amalgamate species (or even genera), which may result in the loss of subtle yet different speciesspecific responses, as shown here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing occurrence of some stress-tolerant and weedy corals (Agaricia, P. astreoides, branching Porites) over the past four decades in the midslope zone corresponds to trends in percent living cover from modern localized surveys of Caribbean coral communities (Green et al, 2008, Estrada-Saldívar et al, 2019, González-Barrios et al, 2021.…”
Section: Challenges With Assessing Long-term Trendsmentioning
confidence: 98%